Diode Laser for Laryngeal Surgery: a Systematic Review - Arroyo,Helena Hotz (2016)
Abstract Introduction The diode laser has been frequently used in the management of laryngeal disorders. The portability and functional diversity of this tool make it a reasonable alternative to conventional lasers. However, whether diode laser has been applied in transoral laser microsurgery, the ideal parameters, outcomes, and adverse effects remain unclear. Objective The main objective of this systematic review is to provide a reliable evaluation of the use of diode laser in laryngeal diseases, trying to clarify its ideal parameters in the larynx, as well as its outcomes and complications. Data Synthesis We included eleven studies in the final analysis. From the included articles, we collected data on patient and lesion characteristics, treatment (diode laser's parameters used in surgery), and outcomes related to the laser surgery performed. Only two studies were prospective and there were no randomized controlled trials. Most of the evidence suggests that the diode laser can be a useful tool for treatment of different pathologies in the larynx. In this sense, the parameters must be set depending on the goal (vaporization, section, or coagulation) and the clinical problem. Conclusion: The literature lacks studies on the ideal parameters of the diode laser in laryngeal surgery. The available data indicate that diode laser is a useful tool that should be considered in laryngeal surgeries. Thus, large, well-designed studies correlated with diode compared with other lasers are needed to better estimate its effects.